An investigation on the role of organizational climate on electronic learning - Hosseinali Aziziha (Management Science Letters, 2014)
This paper presents an empirical investigation on the effect of organizational climate on development of electronic learning in one of Iranian banks named Bank Maskan. In our survey, organizational characteristics include organizational structure, organizational communication, reward and promotion, organizational commitment, risk taking, organizational conflict and team-work. The proposed study uses two questionnaires, one for organizational climate and the other one for electronic learning, in Likert scale. Cronbach alpha for these two questionnaires are calculated as 0.79 and 0.86, respectively. Using Pearson correlation ratio as well as stepwise regression analysis, the study determines that organizational structure, organizational communication, reward and promotion, organizational commitment, risk taking and team-work influence on electronic learning, positively.